Charakterystyka strefy ochronnej Huty Miedzi "Głogów" = Characteristics of the Copper Smelter "Głogów" protection zone - Przewocka, Marta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents the basic issues for the environment protection, regarding the need for protection of the area around "Głogów" Copper Smelter plant. In the early years of the smelter these were considered areas affected by ecological disaster.
Keywords: Huta Miedzi "Głogów"; strefa ochronna; protection zone